(Re)claiming humanity, reclaiming hope: the role of higher education in the 21st century (Revista Nacional de Administración, 2020)
This essay explores questions pertaining to who has had and has the power to define who is human and what it means to be human, and the way higher education is but one of the role-players that define humanity and what it means to be human. It also examines the potential of decoloniality as an alternative and critical onto-epistemology which is  essential for (re)claiming and (re)building humanity. Further pointers for consideration are addressed such as rethinking, epistemic disobedience, entrapment of knowledge production, among others.
Keywords: Educación superior; decolonialidad; humanidad; Sur Global; Giro onto-decolonial